Answer:
<h3>
A = 0.5(2x+6)(6x+13) = 6x² + 49x + 78</h3>
Step-by-step explanation:
H = 2x+6 - the hight
3H = 3(2x+6) - triple the hight
3H-5 = 3(2x+6) - 5 - five less than triple the height
Area of triangle: A = 0.5BH
B = 3(2x+6)-5 = 6x + 18 - 5 = 6x + 13
H = 2x+6
So:
A = 0.5(2x+6)(6x+13) = (x+6)(6x+13) = 6x² + 13x + 36x + 78
A = 6x² + 49x + 78
Answer:
7. A
8. C
9. C
10. A
Step-by-step explanation:
You just have to work each one out. This is very simple.
I think this might be the answer since (a+b) equals 4, and ab= 3. I'm not sure.
a3 + b3
= (4)3+4(3)
= 12+12
= 24